A new species of the ghost shrimp genus Neocallichirus Sakai, 1988 (Decapoda: Axiidea: Callichiridae) from Japan - Komai, Tomoyuki; Naruse, Tohru; Fujita, Yoshihisa (Zootaxa, 2026)
A new species of the ghost shrimp genus Neocallichirus Sakai, 1988 (Axiidea: Callichiridae), N. ceratophthalmus, is described from shoreline habitats of Japan, ranging from Izu Peninsula on the mainland Honshu to southern Ryukyu Islands. This new species is the third known of the genus in Japanese waters with certainty, and is morphologically most similar to N. vaugelasi Dworschak, 2011, currently known with certainty only from the Red Sea. Distinguishing features of N. ceratophthalmus sp. nov. are found in its third maxilliped, major cheliped, and male first pleopod. The study presents a thorough description of the species, encompassing information on its developmental stages, habitat preferences, and molecular phylogenetic analysis. The phylogenetic investigation utilizes data from two mitochondrial markers, specifically the COI and 16S rRNA genes.